Origin of the lumbosacral plexus in Galea spixii (Wagler, 1831) (Rodentia, Caviidae) - Gleidson Benevides Oliveira; Márcio Nogueira Rodrigues; Rejane dos Santos Sousa; Carlos Eduardo Bezerra de Moura; Maria Angélica Miglino; Moacir Franco de Oliveira (Biotemas)
The yellow-toothed cavy is a rodent belonging to the Caviidae family that inhabits the semiarid region of northeastern Brazil. We used 20 cavies that had died of natural causes, obtained from the Reproduction Center of Wild Animals (CEMAS) of the Federal Rural University of the Semi-Arid (UFERSA). The animals were fixed in aqueous solution of 10% formaldehyde and, after 48 hours, they were dissected to visualize plexus. The topographic relations of the lumbosacral plexus were grouped into tables and then they underwent statistical analysis (chi-square test with Yates’ correction). The lumbosacral plexus stemmed from the ventral roots of the last 3 lumbar nerves and the first 3 sacral nerves, corresponding to 65% of the animals under study (L5L6L7S1S2S3). These nerves stemmed from plexus: femoral, obturator, ischiatic, cranial gluteal, caudal gluteal, and pudendal.